The Effect of Liquidity and Solvency on Financial Performance: Moderating Role of Firm Size - Aditio Aditio; Muhammad Nur Rizqi; Harun Faizal (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2026)
This study aims to investigate the relationship between liquidity, solvency, and financial performance, with business size acting as a moderator. Financial performance is one of the most important metrics to consider when evaluating a company's success. This is evidence of the company's adeptness in turning its resources into profit. This study uses a quantitative approach and relies on secondary data gathered from the IDX annual financial statements of food and beverage sub-sector companies from 2020 to 2024. Twenty companies with one hundred observations were generated by the sample approach, which used purposive sampling after data selection by outlier testing and deletion. Data analysis was carried out using EViews 10 software, namely panel data regression and MRA. In contrast to solvency's negative statistically significant link with financial performance, liquidity's positive relationship with financial success is well-established. Moreover, both solvency and liquidity have an impact on financial performance, but the link between the two may be attenuated by increasing the size of the business. According to these results, the link between financial situations and a company's capacity to produce profits is effected by firm size, and the management of current assets and capital structure is a key factor in enhancing financial performance.